The role of alternative polyadenylation in the antiviral innate immune response - Xin Jia (Nature Portfolio, 2017)
RNA processing by alternative polyadenylation (APA) can result in 3′UTR diversity and regulation of target RNA function. Here the authors survey APA in viral infection of macrophages.